Introduction to Gastrointestinal Diseases Vol. 2 - Fichna, Jakub (Springer International Publishing : Imprint: Springer, 2017)
Learn the basics and more of gastrointestinal diseases. Gastrointestinal diseases have become a major medical, social and economic burden worldwide. The larger the number of patients suffering from gastric ulcer and colorectal cancer, the greater the need to properly diagnose and cure. This book is a comprehensive guide through GI diseases, which can be used by practitioners and patients. It will allow: - to explore the mechanisms underlying GI diseases - to accurately diagnose and find the best treatment - to learn how to alleviate GI disease symptoms by changing diet and lifestyle This guide has been written by experts in the field who understand the needs of doctors and their patients. With this book, you will make sure that the GI disease can be properly managed.